CODE-MIXING OF JAVANESE LANGUAGE AND BAHASA INDONESIA IN THE FRIDAY PRAYER SERMON AT MIFTAHUL HIDAYAH MOSQUE, PENDEM VILLAGE, CITY OF BATU, EAST JAVA - Afif Ikhwanul Muslimin (MABASAN, 2020)
Code-mixing phenomenon which appears in different settings and contexts creates interest for investigation. This research is aimed to analyze the elements of code mixing in Friday prayer sermon, the reasons underlying speaker to mix code, and the responses of audience. This is a qualitative research by implementing content analysis. Based on the analysis, the elements of code mixing in the sermon were in the form of words, phrases, and clauses. The reasons causing speaker mixing the code are making the sermon easy listening, making his sermon accepted, understanding listener that old man preferred local language in sermon, matching sermon with social condition, making himself accepted, making ease to deliver the sermon, making sermon more communicative, and making the sermon get in touch with the listeners. Then, based on the questionnaires which were given to 25 respondents, there were 22 people understood the sermones. However, 10 people of them said that the sermones should be delivered in Bahasa Indonesia only. They thought that the sermon would be more easy listening, more understandable, and created more comfortable listening. On the other hand, they thought many listeners were the outsiders of the village. Hence, it is concluded that phenomenon appears to consider context, goal, and audience.